2021
DOI: 10.3390/ijerph18030908
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Data and Machine Learning to Predict Cardiac Amyloidosis

Abstract: (1) Background: Cardiac amyloidosis or “stiff heart syndrome” is a rare condition that occurs when amyloid deposits occupy the heart muscle. Many patients suffer from it and fail to receive a timely diagnosis mainly because the disease is a rare form of restrictive cardiomyopathy that is difficult to diagnose, often associated with a poor prognosis. This research analyses the characteristics of this pathology and proposes a statistical learning algorithm that helps to detect the disease. (2) Methods: The hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…The findings showed that when data vectors profile each disease occurrence, the algorithm may detect disease. The prediction levels demonstrated that this method may be helpful in illness screening procedures on a particular group [ 175 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings showed that when data vectors profile each disease occurrence, the algorithm may detect disease. The prediction levels demonstrated that this method may be helpful in illness screening procedures on a particular group [ 175 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent retrospective analysis of transversal RWS in more than 11,000 patients above 65 years of age has been performed with principal component analysis (PCA), clustering, synthetic minority oversampling, and logistic regression to diagnose cardiac amyloidosis, a rare disease in which poor diagnostic capability results in treatment delays [18]. Analyses of data with high dimensionality, low prevalence, and missing data in EHRs containing structured and unstructured records have relied on the processing and pipelines of data governance and analysis by ML algorithms to transform the investigation of cardiac amyloidosis to meet patient needs.…”
Section: Introductionmentioning
confidence: 99%
“…Early CA diagnostics is usually hindered by indistinguishable clinical presentation and greater awareness of more prevalent hypertrophic diseases and heart failure syndromes. Thus, CA can be considered underdiagnosed, consequently delaying necessary therapeutic measures, reducing quality of life and worsening clinical prognosis [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning is a function of artificial intelligence, used as a promising alternative to overcoming the limitations of traditional prediction approaches [ 17 ]. Recent supervised and unsupervised machine learning approaches have proven highly valuable for the classification, regression and prediction of complex datasets in all industrial sectors, including the medical field of CA diagnostics [ 3 , 18 , 19 ]. For example, promising machine learning aspects have been based on CA-specific laboratory profiles of heart failure patients [ 19 ] or CA-associated ECG mapping [ 18 ].…”
Section: Introductionmentioning
confidence: 99%